Symbiotic Stars in the Era of Modern Ground- and Space-Based Surveys - Jaroslav Merc (Galaxies)
Symbiotic stars, interacting binaries composed of a cool giant and a hot compact companion, exhibit complex variability across the electromagnetic spectrum. Over the past decades, large-scale photometric and spectroscopic surveys from ground- and space-based observatories have significantly advanced their discovery and characterization. These datasets have transformed the search for new symbiotic candidates, providing extensive time-domain information crucial for their classification and analysis. This review highlights recent observational results that have expanded the known population of symbiotic stars, refined classification criteria, and enhanced our understanding of their variability. Despite these advances, fundamental questions remain regarding their long-term evolution, mass transfer and accretion processes, or their potential role as progenitors of Type Ia supernovae. With ongoing and upcoming surveys, the coming years promise new discoveries and a more comprehensive picture of these intriguing interacting systems.